(untitled) (Minerva, 2019)
Review: Andrés Ortega Garrido, Vanguardia y mundo clásico grecolatino en España, Madrid-Frankfurt am Main, Iberoamericana-Vervuert, 2012 (La Casa de la Riqueza. Estudios de la Cultura de España, 22), 623 pp. ISBN 978-848489-575-6 (Iberoamericana) | 978-3-86527-696-4 (Vervuert)